2013
DOI: 10.3892/ijmm.2013.1581
|View full text |Cite
|
Sign up to set email alerts
|

A novel compound heterozygous mutation in the GJB2 gene causing non-syndromic hearing loss in a family

Abstract: Mutations in the GJB2 gene are responsible for up to 50% of cases of non-syndromic recessive hearing loss, with c.35delG, c.167delT and c.235delC being the predominant mutations in many world populations. However, a large number of rare mutations in this gene may also contribute to hearing loss. The aim of the present study was to conduct a clinical and molecular characterization of a Chinese family with non-syndromic hearing loss. Sequence analysis of the GJB2 gene led to the identification of a novel compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…Previous studies proposed that hemichannels structure (hexmer) is crucial for the smooth function of ion channels in the WT‐CX26 protein. Considering that GJB2 c.257C>G (p.T86R) may serve a rare mutation in the second transmembrane domain of the CX26 protein and could be able to convert an uncharged amino acid (threonine) at codon 86 into a positively charged structure (arginine), and logically, it is possible that the rare mutation may cause a functional null protein . Our study showed that the steric hindrance became greater as a result that threonine has been replaced by arginine (Figure ), the evidence indicates that the c.257C>G (p.T86R) mutation in GJB2 gene could impede the dimerization of the CX26 protein.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Previous studies proposed that hemichannels structure (hexmer) is crucial for the smooth function of ion channels in the WT‐CX26 protein. Considering that GJB2 c.257C>G (p.T86R) may serve a rare mutation in the second transmembrane domain of the CX26 protein and could be able to convert an uncharged amino acid (threonine) at codon 86 into a positively charged structure (arginine), and logically, it is possible that the rare mutation may cause a functional null protein . Our study showed that the steric hindrance became greater as a result that threonine has been replaced by arginine (Figure ), the evidence indicates that the c.257C>G (p.T86R) mutation in GJB2 gene could impede the dimerization of the CX26 protein.…”
Section: Discussionmentioning
confidence: 69%
“…Currently, mutations in GJB2 are considered as one of the major causes of nonsyndromic hearing loss following by a dominant or recessive inheritance pattern . The effects of these mutations on the function of CX26 protein could be various and depend on the different positions and types of amino acid substitution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The novel c.240G>C mutation in the GJB2 gene led to a positively charged histidine (His) being substituted for an uncharged glutamine (Gln) at amino acid 80 (p.Q80H), which is located in the TM2 segment of Cx26 protein. Therefore, the rare mutation may generate a functional null protein by disrupting the normal formation of hexamers (21). Three missense mutations (Q80K, Q80P and Q80R) and one nonsense mutation (Q80X) at the same position (The Connexin-deafness Homepage: http://davinci.crg.…”
Section: Discussionmentioning
confidence: 99%
“…GJB2 gene mutations are related to 36.9% of sensory neural hearing loss (SNHL) among children ( Ouyang et al., 2009 ), while the CX26 – the GJB2-coded protein – is involved in the transportation of potassium and serves as the connexon, key to maintaining the balance and stability of inner ear ions. By far, more than 150 mutation sites in the GJB2 genes have been discovered ( http://davinci.crg.es/deafness ) ( Wei et al., 2014 , Zelante et al., 1997 , Petersen and Willems, 2006 , Choi, 2009 , Van Laer et al., 1999 , Welch et al., 2007 , Yan et al., 2006 ).…”
Section: Introductionmentioning
confidence: 99%